Empro care empowering persons with mobility disabilities through the development of prosthetics-orthotics lab & rehab - Pura, Camille Alyssa C. (College of Architecture, University of the Philippines Diliman, 2018)
Dubbed as the "Heart of Health and Wellness in Asia", Quezon City boasts of its various health and wellness facilities. However, as of 2015 census, it is the most populous city in the Philippines. Moreover, 2% of it comprises of PWDs wherein 15% of it have mobility disabilities. With that, the city actually has the highest number of Persons with mobility disabilities in NCR. As said, with the number of health facilities in the city, and although Philippine Orthopedic Center exists, there is actually no existing rehabilitation center in the district that is purely catering to mobility patients, which require a specialized and systematized care and assistance. So, based on the general research and analysis, the city is narrowed down to district 4 and the project type classified to be developed is a Rehabilitation Center with specialized approach. And that project resulted to the development of emPrO Care; empower, embrace. emerge Prosthetics-Orthotics Care. Through the provisions of affordable, appropriate and accessible assistive devices like prosthetic and orthotic equipment, the functional independence of persons with mobility disabilities will be achieved. With emPrO care, appropriate rehabilitation services would be provided and the use of prosthetic devices would be promoted - making majority of PWDs become important contributors to society. The said assistive devices will provide them upward mobility from poverty and render their families and caregivers burdenfree. Dy Ching Bing et al., in their study on amputation, cited the 1990 Profile and Manpower data which revealed that 30.5% PWDs can have gainful employment if provided the appropriate services and the right opportunities, and this is what the project generally aims. The project offers Medical and Rehabilitation care from professional practitioners. It will also include a fabrication laboratory for the assistive devices. However, there are challenges of ensuring sustainable delivery of high technology, low cost prostheses and orthosis to indigent Filipino amputees or with mobility disorder, that not only provide community reintegration but economic empowerment as well These include: accessibility to rural areas, cost, data gathering, training, local raw material utilization, and sustainability according to a research lead by PGH Rehab med department.